2004
DOI: 10.5194/npg-11-485-2004
|View full text |Cite
|
Sign up to set email alerts
|

Radial evolution of intermittent heat flux in solar coronal holes

Abstract: Abstract. Recently, we suggested that the source of ion heating in solar coronal holes is small-scale reconnection events (microflares) at the coronal base. The microflares launch intermittent heat flux up into the corona exciting ion cyclotron waves through a plasma microinstability. The ions are heated by these waves during the microflare bursts and then evolve with no energy input between the bursts. The overall coronal heating by this mechanism is a summed effect of all microflare bursts during the expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…One possible scenario is that the ion-cyclotron waves are generated in the lower corona by small-scale reconnection events as suggested by Axford & McKenzie (1992). They might also be generated locally through a turbulent cascade of low-frequency MHD-type waves towards high-frequency ion-cyclotron waves (Li et al 1999;Hollweg 2000;Ofman et al 2002), or by plasma micro-instabilities driven by current fluctuations of low-frequency MHD modes (Markovskii 2001), or by an intermittent electron heat flux accompanying microflare events (Markovskii & Hollweg 2004). Voitenko & Goossens (2002) further suggested that plasma outflows from reconnection sites in microflares could create ionbeam configurations in the surrounding plasma, and thus provide free energy for driving kinetic micro-instabilities through ion-cyclotron resonance and the Cerenkov effect.…”
Section: Introductionmentioning
confidence: 99%
“…One possible scenario is that the ion-cyclotron waves are generated in the lower corona by small-scale reconnection events as suggested by Axford & McKenzie (1992). They might also be generated locally through a turbulent cascade of low-frequency MHD-type waves towards high-frequency ion-cyclotron waves (Li et al 1999;Hollweg 2000;Ofman et al 2002), or by plasma micro-instabilities driven by current fluctuations of low-frequency MHD modes (Markovskii 2001), or by an intermittent electron heat flux accompanying microflare events (Markovskii & Hollweg 2004). Voitenko & Goossens (2002) further suggested that plasma outflows from reconnection sites in microflares could create ionbeam configurations in the surrounding plasma, and thus provide free energy for driving kinetic micro-instabilities through ion-cyclotron resonance and the Cerenkov effect.…”
Section: Introductionmentioning
confidence: 99%
“…Though we have emphasized the possibility of a turbulent cascade, there are other possible sources of waves in the resonant range. For example, Markovskii and Hollweg [2002, 2004a, 2004b] considered instabilities driven by intermittent bursts of large electron heat flux in the corona; the electron heat flux was in turn envisioned as being generated by nanoflares at the coronal base. The instabilities were electrostatic or electromagnetic ion‐cyclotron waves.…”
Section: Discussionmentioning
confidence: 99%